Pelatihan Meningkatkan Pemahaman Pelaku UMKM Menyusun Laporan Keuangan Sederhana(UMKM Kompeten di Bekasi) - R. Rosiyana Dewi; Seto Makmur Wibowo; Mauliddini Nadifah (Penerbit Goodwood, 2022)
Purpose: Bookkeeping is one of the important factors that aim to develop MSMEs. Simple bookkeeping is quite important for the progress of their own business. One of the causes of MSMEs being difficult to develop is a poor accounting system. This is due to the government's lack of attention, and there are still many MSME actors who are reluctant to think about complicated things such as accounting and financial management issues. Currently, MSME actors are only limited to thinking about how to get profits so that their business or MSMEs can run and develop. To that end, the Indonesian Institute of Accountants (IAI) has prepared SAK-EMKM (Financial Accounting Standards for Micro, Small and Medium Entities) to facilitate MSMEs in compiling their financial reports. Method: This community service (PKM) was held online in March 2021 with the participants from business people in the convection and culinary fields. PKM is carried out by lecturers, students, alumni and staff. Result: The results of this PKM activity resulted that members of the KOMPETeN MSME group did not understand well about the types of financial statements and their benefits and how to prepare them, especially the preparation of income statements in accordance with generally accepted accounting standards. Conclusion: This community service (PKM) help the KOMPETeN MSME group to prepare simple financial statement.